Transition metal compound nano array loaded copper nanocluster electrode as well as preparation method and application thereof

By constructing a copper nanocluster electrode supported by transition metal compound nanoarrays, the problems of low catalytic activity and poor selectivity in the electrocatalytic reduction nitrate ammonia production reaction are solved, and efficient ammonia generation and high Faraday efficiency are achieved.

CN119663355APending Publication Date: 2025-03-21SUN YAT SEN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411861706.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing metal copper materials have low catalytic activity and poor selectivity in the electrocatalytic reduction nitrate ammonia production reaction, which hinders its practical promotion and application in the field of electrocatalytic reduction nitrate ammonia production.

Method used

By placing the current collector in a mixed solution containing a transition metal salt and a precipitant for solvothermal reaction, a nanoarray precursor was obtained and calcined in the presence of a heat conversion source substance to obtain a transition metal compound nanoarray material. Finally, it was soaked in the copper salt solution to achieve the loading of the copper nanoclusters, and a copper nanocluster electrode supported by the transition metal compound nanoarray was constructed.

Benefits of technology

The electrode showed excellent ammonia production rate and Faraday efficiency in the electrocatalytic reduction of nitrate ammonia production reaction, with an ammonia production rate of at least 0.958 mmol/(h·cm2) and a Faraday efficiency of at least 97.2%, which significantly improved the catalytic performance of metal copper materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005193355500000161
    Figure BDA0005193355500000161
  • Figure BDA0005193355500000162
    Figure BDA0005193355500000162
  • Figure HDA0005193355510000011
    Figure HDA0005193355510000011
Patent Text Reader

Abstract

The invention belongs to the technical field of electrocatalytic reduction, and particularly relates to a copper nanocluster electrode loaded by a transition metal compound nanoarray and a preparation method and application of the copper nanocluster electrode. The nano array electrode takes a current collector as a carrier, the nano array electrode is prepared through solvothermal reaction, anaerobic roasting reaction and spontaneous oxidation-reduction reaction in sequence, and the preparation method is simple to operate, green and environment-friendly, and easy for large-scale production. In the electrode material, the copper nanocluster can effectively reduce nitrate into nitrite; the transition metal compound can effectively dissociate the active hydrogen of the aquatic product; and meanwhile, an intimate heterogeneous interface is beneficial to rapid transfer of active hydrogen generated by a transition metal compound to a copper site through anti-hydrogen overflow, and nitrite is effectively reduced to obtain ammonia. Benefited from the structural advantages of the composition and the unique anti-hydrogen overflow effect, the obtained electrode can show excellent ammonia production rate and Faraday efficiency when being applied to the reaction for preparing ammonia by electro-catalysis nitrate reduction, and has great application prospects in the field of electrochemical treatment of nitrate-containing wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrocatalytic electrodes, and more specifically, to a transition metal compound nanoarray-loaded copper nanocluster electrode and a preparation method and application thereof. Background Art

[0002] Ammonia (NH3) is an indispensable raw material for both industrial development and agricultural production, and is often used in the manufacture of fertilizers, medicines, weapons, and textiles. At the same time, in the context of global carbon neutrality, ammonia is not only a clean fuel that can achieve zero carbon emissions, but also an excellent hydrogen storage carrier, with great potential in energy conversion and hydrogen storage applications. However, the industrial production of ammonia is heavily dependent on the Haber-Bosch process operating under high temperature and high pressure conditions. The energy consumed by this process each year accounts for about 2% of the global total, and about 620Mt of carbon emissions are generated each year, which puts a great burden on global energy utilization and the ecological environment. Therefore, it is very important to explore new green and environmentally friendly methods for ammonia synthesis.

[0003] The electrocatalytic reduction of nitrate to ammonia (NO3RR) technology is clean, efficient and sustainable, and is a promising green means of producing ammonia. Catalysts are the key elements of the electrocatalytic reduction of nitrate to ammonia. Currently, among various transition metals, copper (Cu) has been widely studied as an electrocatalyst for NO3RR due to its low cost, unique electronic structure and good catalytic efficiency. However, the problems of low NH3 yield and poor selectivity of metallic copper materials have hindered their practical application in the field of electrocatalytic reduction of nitrate to ammonia. Therefore, it is of great significance to develop highly active and selective metallic copper materials for the field of electrocatalytic reduction of nitrate to ammonia. Summary of the invention

[0004] Aiming at the defects and shortcomings of existing metallic copper materials, such as low catalytic activity and poor selectivity in the electrocatalytic reduction of nitrate to produce ammonia reaction (NO3RR), a transition metal compound nanoarray-loaded copper nanocluster electrode is provided.

[0005] The purpose of the present invention is to provide a method for preparing a transition metal compound nanoarray-loaded copper nanocluster electrode.

[0006] Another object of the present invention is to provide an application of the transition metal compound nanoarray-supported copper nanocluster electrode in the electrocatalytic reduction of nitrates to produce ammonia.

[0007] Another object of the present invention is to provide the use of the transition metal compound nanoarray-loaded copper nanocluster electrode in electrochemical treatment of nitrate-containing wastewater.

[0008] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0009] The present invention provides a method for preparing a transition metal compound nanoarray-loaded copper nanocluster electrode, which specifically comprises the following steps:

[0010] S1, placing the current collector in a mixed solution containing a transition metal salt and a precipitant, performing a solvothermal reaction, and post-processing to obtain a nanoarray precursor;

[0011] S2, taking the nanoarray precursor obtained in step S1, adding a heat conversion source material, and calcining under oxygen-free conditions to obtain a transition metal compound nanoarray material;

[0012] S3, taking the transition metal compound nanoarray material obtained in step S2, and soaking it in a copper salt solution to obtain a transition metal compound nanoarray-loaded copper nanocluster electrode;

[0013] In step S2, the heat conversion source material is a boron source, a carbon source, a nitrogen source or a phosphorus source.

[0014] The present invention places a current collector in a mixed solution of a transition metal salt and a precipitant to carry out a solvothermal reaction to obtain a hydroxide nanoarray precursor, and then roasts it in the presence of a heat conversion source material to carry out a high-temperature conversion to obtain a transition metal compound nanoarray material. The transition metal compound nanoarray material is a transition metal boride / carbide / nitride / phosphide nanoarray material with reducing properties. Finally, it is immersed in a copper salt solution, and the copper nanoclusters are uniformly loaded on the transition metal compound nanoarray through a spontaneous oxidation-reduction reaction between the transition metal compound nanoarray material with reducing properties and copper ions, so that the copper nanocluster electrodes loaded with the transition metal compound nanoarray are obtained.

[0015] In the electrode described in the present invention, the copper nanoclusters help to reduce nitrate to nitrite, and the transition metal compound material helps to split water to produce active hydrogen (*H). At the same time, the intimate heterogeneous interface between the transition metal compound nanoarray and the copper nanoclusters helps the active hydrogen produced by the transition metal compound nanoarray to be quickly transferred to the copper site through anti-hydrogen overflow, thereby strengthening the active hydrogen (*H) kinetics, thereby enhancing the deoxygenation and hydrogenation process of the NO3RR process, effectively reducing nitrite to obtain ammonia, and improving the ammonia production rate and Faraday efficiency of the metal copper material.

[0016] Preferably, in step S1, the transition metal in the transition metal salt is selected from at least one of Ni, Co, Fe, Mn, Sc, Ti, V, Cr, Cu, Mo, Cd, W, Y, Zr, Ce, Ga, In, Ge, and Sn. Ni, Co, Fe, and Mn-based compounds have good ability to catalyze water splitting to produce active hydrogen (*H), while Mo, Ce, Zr, W, Sc, Ti, V, Cr, Y, Nb, and Tc are some conventional dopants, and appropriate doping is beneficial to improving catalytic activity.

[0017] More preferably, in step S1, the transition metal in the transition metal salt is a main transition metal, or a main transition metal and a doped transition metal, the main transition metal is selected from one or more of Ni, Co, Fe, and Mn; the doped transition metal is selected from at least one of V, Sc, Mn, Cr, Ti, W, Y, and Zr.

[0018] Furthermore, in step S1, when the transition metal in the transition metal salt is a main transition metal and a doped transition metal, the molar ratio of the doped transition metal to the main transition metal is 1:(1-100). Preferably, the molar ratio of the doped transition metal to the main transition metal is 1:(1-20); specifically, it can be 1:1, 1:2, 1:4, 1:8, 1:9, 1:10, 1:19, 1:20, etc., or an interval range formed by any of the above ratios, such as 1:(1-9), 1:(1-10), 1:(1-19), etc., and the present invention is not limited thereto.

[0019] Preferably, in step S1, the transition metal salt is selected from one or more of nitrates, acetates, chlorides, carbonates and sulfates.

[0020] Furthermore, in step S1, the precipitant is selected from at least one of sodium hydroxide, potassium hydroxide, ammonia water, sodium carbonate, sodium bicarbonate, urea, hexamethylenetetramine, and sodium oxalate.

[0021] Further, in step S1, the molar concentration of the transition metal salt is 0.001 to 10 mol / L; preferably, the concentration of the transition metal salt is 0.01 to 5 mol / L; more specifically, the concentration of the transition metal salt is 0.01 mol / L, 0.03 mol / L, 0.10 mol / L, 0.20 mol / L, 1 mol / L, 2 mol / L, 3 mol / L, 5 mol / L, or an interval range formed by any of the above values, such as 0.01 to 3 mol / L, 0.1 to 2 mol / L, 0.01 to 2 mol / L, 0.03 to 5 mol / L, etc., but the present invention is not limited thereto.

[0022] Further, in step S1, the molar ratio of the transition metal salt to the precipitant is 1:(0.2-20). Preferably, the molar ratio of the transition metal salt to the precipitant is 1:(0.2-16). Specifically, it can be 1:0.2, 1:2, 1:4, 1:8, 1:16, or an interval range formed by any of the above values, such as 1:(1-2), 1:(1-4), 1:(2-2), 1:(0.2-8), etc., and the present invention is not limited thereto.

[0023] Furthermore, in step S1, the current collector is carbon cloth, carbon paper or a metal current collector.

[0024] Preferably, the metal current collector is metal foam, metal foil, metal plate or metal mesh; more preferably, the metal of the metal current collector is Fe, Co, Ni, Zn, Al, Ti or stainless steel.

[0025] Further, in step S1, the temperature of the solvent thermal reaction is 50 to 250° C. Preferably, in step S1, the temperature of the solvent thermal reaction is 60 to 200° C. Specifically, it can be 60° C., 80° C., 100° C., 130° C., 150° C., 180° C., 200° C., or an interval range formed by any of the above values, such as 60 to 100° C., 130 to 200° C., 130 to 150° C., 80 to 180° C., etc., but the present invention is not limited thereto.

[0026] Furthermore, in step S1, the solvent thermal reaction time is 1 to 24 hours. Specifically, it can be 1 hour, 2 hours, 5 hours, 8 hours, 12 hours, 24 hours, or an interval range formed by any of the above values, such as 1 to 5 hours, 2 to 12 hours, 2 to 24 hours, etc., and the present invention is not limited thereto.

[0027] Furthermore, in step S1, the solvent in the mixed solution is one or more of water, methanol, ethanol, propanol, butanol, isopropanol, ethylene glycol, propylene glycol, 1,4-butanediol, 1,2,4-butanetriol, 1,6-hexanediol, pentanediol, glycerol, benzyl alcohol, cyclohexanol, acetone, diethylene glycol, triethylene glycol, acetonitrile, methyl acetate, and ethyl acetate.

[0028] In the present invention, the heat conversion source material may be in a gaseous state or a solid state. When the heat conversion source material is in a solid state, in step S2, the calcination is performed in an inert gas atmosphere.

[0029] Furthermore, the inert gas is selected from at least one of nitrogen (N2), argon (Ar), and helium (He).

[0030] Further, the gas flow rate of the inert gas and the gaseous heat conversion source material is 0.1 to 200 mL / min; preferably, the gas flow rate of the inert gas is 2 to 100 mL / min. Specifically, it can be 2 mL / min, 5 mL / min, 10 mL / min, 20 mL / min, 30 mL / min, 50 mL / min, 70 mL / min, 100 mL / min, or an interval range formed by any of the above values, such as 2 to 100 mL / min, 5 to 100 mL / min, 2 to 5 mL / min, etc., but the present invention is not limited thereto.

[0031] Preferably, the boron source is one or both of sodium borohydride and boron powder; the carbon source is one or more of methane, ethylene, and acetylene; the nitrogen source is one or both of urea and melamine; and the phosphorus source is one or both of sodium dihydrogen hypophosphite and red phosphorus.

[0032] Preferably, in step S2, the calcination temperature is 180-1000°C. Specifically, the calcination temperature is 180°C, 200°C, 250°C, 300°C, 350°C, 400°C, 500°C, 600°C, 700°C, , 800°C, 1000°C, or an interval range formed by any of the above values, such as 180-400°C, 180-800°C, 200-1000°C, etc., but the present invention is not limited thereto.

[0033] Furthermore, the calcination time is 1 to 24 hours; preferably, the calcination time is 1 to 8 hours. Specifically, the calcination time can be 1 hour, 2 hours, 3 hours, 4 hours, 6 hours, 8 hours, or an interval range formed by any of the above values, such as 1 to 6 hours, 2 to 6 hours, 2 to 8 hours, etc., and the present invention is not limited thereto.

[0034] Furthermore, in step S2, when the thermal conversion source material is in a solid state, the mass ratio of the nanoarray precursor to the thermal conversion source material is 1:(1-200); preferably, the mass ratio of the nanoarray precursor to the thermal conversion source material is 1:(1-150). Specifically, it can be 1:1, 1:5, 1:10, 1:20, 1:50, 1:100, 1:150, or an interval range formed by any of the above ratios, such as 1:(5-150), 1:(10-150), 1:(20-150), etc., and the present invention is not limited thereto.

[0035] Further, in step S2, the heating rate of the calcination is 1 to 20°C / min; preferably, the heating rate of the calcination is 1 to 10°C / min. Specifically, it can be 1°C / min, 2°C / min, 3°C / min, 5°C / min, 8°C / min, 10°C / min, or an interval range formed by any of the above values, such as 2 to 5°C / min, 2 to 8°C / min, 3 to 8°C / min, etc., but the present invention is not limited thereto.

[0036] Furthermore, in step S3, the copper salt is one or more of copper sulfate, copper nitrate, copper chloride, and copper acetate.

[0037] Furthermore, in step S3, the solvent in the copper salt solution is selected from one or more of water, methanol, ethanol, isopropanol, ethylene glycol, 1,4-butanediol, 1,2,4-butanetriol, 1,6-hexanediol, pentanediol, glycerol, toluene, acetonitrile, acetone, methyl acetate, and ethyl acetate.

[0038] Further, in step S3, the concentration of the copper salt solution is 0.001mol / L~5mol / L; preferably, it can be 0.01mol / L~3mol / L; specifically, it can be 0.01mol / L, 0.1mol / L, 0.5mol / L, 0.8mol / L, 1mol / L, 2mol / L, 3mol / L, or an interval range formed by any of the above values, such as 0.01mol / L~0.1mol / L, 0.01mol / L~0.5mol / L, 0.1mol / L~3mol / L, etc., but the present invention is not limited thereto.

[0039] Further, in step S3, the soaking time can be 0.01h to 48h; preferably, it can be 0.5h to 24h; specifically, it can be 0.5h, 2h, 6h, 12h, 18h, 24h, or an interval range formed by any of the above values, such as 0.5h to 2h, 2h to 6h, 2h to 24h, etc., but the present invention is not limited thereto.

[0040] Preferably, in step S1, the post-treatment is cooling, washing and drying.

[0041] Preferably, in step S3, after soaking in the copper salt solution, washing and drying are required.

[0042] At the same time, the present invention also claims to protect the transition metal compound nanoarray-loaded copper nanocluster electrode prepared by the preparation method.

[0043] In addition, the present invention also claims to protect the use of the transition metal compound nanoarray-loaded copper nanocluster electrode in the electrocatalytic reduction of nitrate to produce ammonia.

[0044] Furthermore, the present invention also protects the use of the transition metal compound nanoarray-loaded copper nanocluster electrode in the electrochemical treatment of nitrate-containing wastewater.

[0045] The present invention has the following beneficial effects:

[0046] The present invention uses a current collector as a carrier, and in situ grows a nanoarray precursor on the carrier through a solvent thermal reaction, and then roasts it in the presence of a heat conversion source material to perform a high-temperature conversion to obtain a transition metal compound nanoarray material with a reducing property. Finally, through the spontaneous redox reaction between the reducing metal species in the transition metal compound and the copper ions, the copper ions are reduced to obtain copper nanoclusters loaded on the array material, that is, a transition metal compound nanoarray-loaded copper nanocluster electrode is obtained. Based on the above-mentioned compositional structural advantages and the unique anti-hydrogen overflow effect, the electrode constructed by the present invention exhibits excellent ammonia production rate and Faraday efficiency in the electrocatalytic reduction of nitrate to produce ammonia, and the ammonia production rate is at least 0.958mmol / (h·cm 2 ), the Faraday efficiency is at least 97.2%, and most of the electric energy actually consumed by electrocatalysis is used to produce NH3 rather than other substances. The electrode material prepared by the present invention has high selectivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 This is the SEM image of the CC / FeB@Cu nanoarray electrode prepared in Example 1.

[0048] Figure 2 This is the SEM image of the NF / CoVP@Cu nanoarray electrode prepared in Example 2.

[0049] Figure 3 This is the SEM image of the IF / NiScC@Cu nanoarray electrode prepared in Example 3.

[0050] Figure 4 This is the SEM image of the CP / FeMnCrN@Cu nanoarray electrode prepared in Example 4.

[0051] Figure 5 This is the SEM image of the TP / CoTiWB@Cu nanoarray electrode prepared in Example 5.

[0052] Figure 6 This is the SEM image of the SS / NiYZrP@Cu nanoarray electrode prepared in Example 6.

[0053] Figure 7 The LSV diagrams of the array electrodes of Example 1 and Comparative Examples 1 and 2 in the electrocatalytic reduction of nitrate to produce ammonia.

[0054] Figure 8The LSV diagrams of the array electrodes of Example 2 and Comparative Examples 3 and 4 in the electrocatalytic reduction of nitrate to produce ammonia.

[0055] Fig. 9 The LSV diagrams of the array electrodes of Example 3 and Comparative Examples 5 and 6 in the electrocatalytic reduction of nitrate to produce ammonia.

[0056] Fig.10 The LSV diagrams of the array electrodes of Example 4 and Comparative Examples 7 and 8 in the electrocatalytic reduction of nitrate to produce ammonia.

[0057] Fig.11 The LSV diagrams of the array electrodes of Example 5 and Comparative Examples 9 and 10 in the electrocatalytic reduction of nitrate to produce ammonia.

[0058] Fig.12 The LSV diagrams of the array electrodes of Example 6 and Comparative Examples 11 and 12 in the electrocatalytic reduction of nitrate to produce ammonia. DETAILED DESCRIPTION

[0059] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0060] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0061] Example 1CC / FeB@Cu nanoarray electrode

[0062] The preparation method of the CC / FeB@Cu nanoarray electrode comprises the following steps:

[0063] S1. Take 54 g (200 mmol) of ferric chloride hexahydrate (FeCl3·6H2O) and 56.1 g (400 mmol) of hexamethylenetetramine (HMTA) and dissolve them in 40 mL of ultrapure water to form a uniform mixed solution. After fully stirring on a stirrer for 2 h (the stirrer speed is 600 rpm) to obtain a mixed solution, immerse 2 pieces of 5×6 cm pretreated carbon cloth (CC), transfer to a high-pressure reactor, seal and place in a blast drying oven for solvent thermal reaction, react at 200° C. for 1 h, wait for it to cool naturally after the reaction is completed, wash the cooled material with ultrapure water and anhydrous ethanol for 3 times respectively, and dry it in a blast drying oven at 60° C. for 6 h to obtain a Fe-OH nanoarray precursor loaded on a CC current collector;

[0064] S2, placing the Fe-OH nanoarray precursor loaded on the CC current collector obtained in step S1 in the downstream of the tube furnace, placing the boron source sodium borohydride in the upstream, the mass ratio of Fe-OH to sodium borohydride is 1:150, the N2 flow rate is controlled at 2 mL / min, the temperature is increased from room temperature to 1000°C at a heating rate of 8°C / min, and heat-treated at 1000°C for 6 hours. After natural cooling, the FeB nanoarray material loaded on the CC current collector is obtained;

[0065] S3. Soak the FeB nanoarray loaded on the CC current collector obtained in step S2 in a 0.5 mol / L copper chloride (CuCl2·2H2O) ethanol solution for 10 min, then rinse with ethanol three times, and dry in a forced air drying oven at 60°C for 6 h to obtain a FeB@Cu nanoarray electrode loaded on the CC current collector.

[0066] Material Characterization:

[0067] The SEM material morphology of the obtained product is as follows: Figure 1 As shown, the figure shows the uniformly distributed nanosheet structure on the CC current collector.

[0068] Example 2 NF / CoVP@Cu nanoarray electrode

[0069] The preparation method of the NF / CoVP@Cu nanoarray electrode comprises the following steps:

[0070] S1, 0.505g (1.8mmol) of cobalt sulfate heptahydrate (CoSO4·7H2O), 0.033g (0.2mmol) of vanadyl sulfate hydrate (VOSO4·xH2O) and 1.92g (32mmol) of urea (CH4N2O) were dissolved in 20mL of ultrapure water, and the mixture was stirred on a stirrer for 2h (the stirrer speed was 500rpm) to obtain a mixed solution, and then immersed in 2 pieces of 1×3cm pretreated nickel foam (NF), transferred to a high-pressure reactor, sealed and placed in a blast drying oven for solvent thermal reaction, reacted at 150°C for 5h, and allowed to cool naturally after the reaction was completed. The cooled material was washed with ultrapure water and anhydrous ethanol for 3 times respectively, and dried at 60°C in a blast drying oven for 8h to obtain the CoV-OH nanoarray precursor loaded on the NF current collector;

[0071] S2, placing the NF current collector-loaded CoV-OH nanoarray precursor obtained in step S1 in the downstream of the tube furnace, placing the phosphorus source sodium dihydrogen hypophosphite in the upstream, the mass ratio of CoV-OH to sodium dihydrogen hypophosphite is 1:20, the Ar flow rate is controlled at 2 mL / min, the temperature is increased from room temperature to 180°C at a heating rate of 2°C / min, and heat-treated at 180°C for 1h. After natural cooling, the NF current collector-loaded CoVP nanoarray material is obtained;

[0072] S3. Soak the NF current collector-loaded CoVP nanoarray precursor obtained in step S2 in a 0.1 mol / L copper acetate (Cu(CH3COO)2·H2O) aqueous solution for 30 min, then rinse with ethanol three times, and dry in a forced air drying oven at 60°C for 6 h to obtain a CoVP@Cu nanoarray electrode loaded on the NF current collector.

[0073] Material Characterization:

[0074] The SEM material morphology of the obtained product is as follows Figure 2 As shown, the figure shows the uniformly distributed nanowire structure on the NF current collector.

[0075] Example 3IF / NiScC@Cu nanoarray electrode

[0076] The preparation method of the IF / NiScC@Cu nanoarray electrode comprises the following steps:

[0077] S1. Dissolve 0.995 g (4 mmol) of nickel acetate tetrahydrate (NiC4H6O4·4H2O), 0.259 g (1 mmol) of scandium chloride hydrate (ScCl3·6H2O) and 1.402 g (10 mmol) of hexamethylenetetramine (HMTA) in 20 mL of ultrapure water, stir the mixture on a stirrer for 0.5 h (the stirrer speed is 500 rpm) to obtain a mixed solution, immerse 2 pieces of 1×3 cm pretreated foam iron (IF), transfer to a high-pressure reactor, seal it and place it in a forced air drying oven for solvent thermal reaction, react at 130°C for 8 h, and allow it to cool naturally after the reaction is completed. The cooled material is washed with ultrapure water and anhydrous ethanol for 3 times respectively, and dried at 60°C in a forced air drying oven for 12 h to obtain a NiSc-OH nanoarray precursor loaded on the IF current collector;

[0078] S2, placing the NiSc-OH nanoarray precursor loaded on the IF current collector obtained in step S1 in a tube furnace, under a methane atmosphere, controlling the flow rate at 30 mL / min, raising the temperature from room temperature to 700°C at a heating rate of 5°C / min, heat treating at 700°C for 2 h, and naturally cooling to obtain a NiScC nanoarray material loaded on the IF current collector;

[0079] S3. Soak the NiScC nanoarray precursor loaded on the IF current collector obtained in step S2 in a 0.8 mol / L copper sulfate (CuSO4·5H2O) aqueous solution for 40 min, then rinse with ethanol three times, and dry in a forced air drying oven at 60°C for 6 h to obtain a NiScC@Cu nanoarray electrode loaded on the IF current collector.

[0080] Material Characterization:

[0081] The SEM morphology of the obtained product is characterized as follows Figure 3 As shown, the figure shows the uniformly distributed nanosheet structure on the IF current collector.

[0082] Example 4 CP / FeMnCrN@Cu nanoarray electrode

[0083] The preparation method of the CP / FeMnCrN@Cu nanoarray electrode comprises the following steps:

[0084] S1. Take 54g (450mmol) of ferric chloride nonahydrate (Fe(NO3)3·6H2O), 6.275g (25mmol) of manganese nitrate tetrahydrate (Mn(NO3)2·4H2O), 6.75g (25mmol) of chromium chloride hexahydrate (CrCl3·6H2O) and 5.611g (100mmol) of potassium hydroxide (KOH), dissolve them in 1000mL of ultrapure water, stir them on a stirrer for 3h (the stirrer speed is 500rpm) to obtain a mixed solution, immerse 3 pieces of 6×3cm pretreated carbon paper (CP), transfer them to a high-pressure reactor, seal them and place them in a forced air drying oven for solvent thermal reaction, react at 180℃ for 12h, wait for them to cool naturally after the reaction is completed, wash the cooled material with ultrapure water and anhydrous ethanol for 3 times respectively, and dry them in a forced air drying oven at 60℃ for 12h to obtain a FeMnCr-OH nanoarray precursor loaded on the CP current collector;

[0085] S2, placing the FeMnCr-OH nanoarray precursor loaded on the CP current collector obtained in step S1 in the downstream of the tube furnace, placing urea in the upstream, the mass ratio of FeMnCr-OH to urea is 1:20, the N2 flow rate is controlled at 2 mL / min, the temperature is increased from room temperature to 400°C at a heating rate of 5°C / min, and heat-treated at 400°C for 3h. After natural cooling, the FeMnCrN nanoarray material loaded on the CP current collector is obtained;

[0086] S3. Soak the FeMnCrN nanoarray electrode loaded on the CP current collector obtained in step S2 in a 1 mol / L copper nitrate (Cu(NO3)2·3H2O) methanol solution for 60 min, then rinse with ethanol three times, and dry in a forced air drying oven at 60°C for 6 h to obtain a FeMnCrN@Cu nanoarray electrode loaded on the CP current collector.

[0087] Material Characterization:

[0088] The SEM material morphology of the obtained product is as follows: Figure 4 As shown, the figure shows the uniformly distributed nanosheet structure on the CP current collector.

[0089] Example 5 TP / CoTiWB@Cu nanoarray electrode

[0090] The preparation method of the TP / CoTiWB@Cu nanoarray electrode comprises the following steps:

[0091] S1, 0.125g (0.5mmol) of cobalt acetate (Co(CH3COO)2·4H2O), 0.076g (0.4mmol) of titanium chloride (TiCl4), 0.033g (0.1mmol) of sodium tungstate (Na2WO4·2H2O) and 0.561g (4mmol) of hexamethylenetetramine (HMTA) were dissolved in 30mL of ultrapure water, and the mixture was stirred on a stirrer for 1h (the stirrer speed was 500rpm) to obtain a uniform mixed solution, and then immersed in a 1×3cm pretreated titanium plate (TP), and the mixed solution was transferred to a high-pressure reactor with a polytetrafluoroethylene liner, sealed and placed in a forced air drying oven for solvent thermal reaction, reacted at 150°C for 12h, and allowed to cool naturally after the reaction was completed. The cooled material was washed with ultrapure water and anhydrous ethanol, and dried in a forced air drying oven at 60°C for 12h to obtain a TP current collector loaded CoTiW-OH nanoarray precursor;

[0092] S2, placing the TP current collector loaded with CoTiW-OH nanoarray precursor obtained in step S1 in the downstream of the tube furnace, placing the boron powder in the upstream, the mass ratio of CoTiW-OH to boron powder is 1:100, the N2 flow rate is controlled at 5 mL / min, the temperature is increased from room temperature to 800°C at a heating rate of 2°C / min, and heat treated at 800°C for 2h. After natural cooling, the CoTiWB nanoarray material loaded on the TP current collector is obtained;

[0093] S3. Soak the CoTiWB nanoarray electrode loaded on the TP current collector obtained in step S2 in a 0.01 mol / L copper chloride (CuCl2·2H2O) aqueous solution for 20 min, then rinse with ethanol three times, and dry in a forced air drying oven at 60°C for 6 h to obtain a CoTiWB@Cu nanoarray electrode loaded on the TP current collector.

[0094] Material Characterization:

[0095] The SEM morphology of the obtained product is characterized as follows Figure 5 As shown, the figure shows the uniformly distributed nanorod-like structures on the TP current collector.

[0096] Example 6SS / NiYZrP@Cu nanoarray electrode

[0097] The preparation method of the SS / NiYZrP@Cu nanoarray electrode comprises the following steps:

[0098] S1. Dissolve 1.902 g (8 mmol) of nickel trichloride hexahydrate (NiCl2·6H2O), 0.304 g (1 mmol) of yttrium chloride hexahydrate (YCl3·6H2O), 0.233 g (1 mmol) of cerium chloride heptahydrate (ZrCl4·7H2O) and 1.402 g (10 mmol) of hexamethylenetetramine (HMTA) in 50 mL of ultrapure water, stir the mixture on a stirrer for 3 h (the stirrer speed is 500 rpm) to obtain a mixed solution, immerse 3 pieces of 2×3 cm pretreated stainless steel sheets (SS), transfer to a high-pressure reactor, seal it and place it in a forced air drying oven for solvothermal reaction, react at 150°C for 24 h, and allow it to cool naturally after the reaction is completed. The cooled material is washed with ultrapure water and anhydrous ethanol for 3 times respectively, and dried at 60°C in a forced air drying oven for 6 h to obtain a NiYZr-OH nanoarray precursor supported on the SS current collector;

[0099] S2, placing the SS current collector loaded with NiYZr-OH nanoarray precursor obtained in step S1 in the downstream of the tube furnace, placing red phosphorus in the upstream, the mass ratio of NiYZr to red phosphorus is 1:50, the N2 flow rate is controlled at 2mL / min, the temperature is increased from room temperature to 200°C at a heating rate of 3°C / min, and heat treated at 200°C for 1h. After natural cooling, the NiYZrP nanoarray material loaded on the SS current collector is obtained;

[0100] S3. Soak the NiYZrP nanoarray electrode loaded on the SS current collector obtained in step S2 in a 1.5 mol / L copper sulfate (CuSO4·5H2O) aqueous solution for 50 min, then rinse with ethanol three times, and dry in a forced air drying oven at 60°C for 6 h to obtain a NiYZrP@Cu nanoarray electrode loaded on the SS current collector.

[0101] Material Characterization:

[0102] The SEM material morphology of the obtained product is as follows Figure 6 As shown, the figure shows the uniformly distributed nanosheet structure on the SS current collector.

[0103] Comparative Example 1CC / FeB Electrode

[0104] The preparation method of the CC / FeB nanoarray electrode comprises the following steps:

[0105] S1. Take 54 g (200 mmol) of ferric chloride hexahydrate (FeCl3·6H2O) and 56.1 g (400 mmol) of hexamethylenetetramine (HMTA) and dissolve them in 40 mL of ultrapure water to form a uniform mixed solution. After fully stirring on a stirrer for 2 h (the stirrer speed is 600 rpm) to obtain a mixed solution, immerse 2 pieces of 5×6 cm pretreated carbon cloth (CC), transfer to a high-pressure reactor, seal and place in a blast drying oven for solvent thermal reaction, react at 200° C. for 1 h, wait for it to cool naturally after the reaction is completed, wash the cooled material with ultrapure water and anhydrous ethanol for 3 times respectively, and dry it in a blast drying oven at 60° C. for 6 h to obtain a Fe-OH nanoarray precursor loaded on a CC current collector;

[0106] S2. Place the Fe-OH nanoarray precursor loaded on the CC current collector obtained in step S1 in the downstream of the tube furnace, and place the boron source sodium borohydride in the upstream, the mass ratio of Fe-OH to sodium borohydride is 1:150, the N2 flow rate is controlled at 2 mL / min, and the temperature is increased from room temperature to 1000°C at a heating rate of 8°C / min. Heat treatment is performed at 1000°C for 6 hours. After natural cooling, the FeB nanoarray electrode loaded on the CC current collector is obtained.

[0107] Compared with Example 1, Comparative Example 1 does not involve immersing in a copper salt solution, and the remaining steps are consistent with those of Example 1.

[0108] Comparative Example 2CC / Cu Electrode

[0109] The preparation method of the CC / Cu electrode comprises the following steps:

[0110] S1. Take 50 mmol of copper chloride (CuCl2·2H2O) and dissolve it in 100 mL of anhydrous ethanol to form a uniform mixed solution;

[0111] S2. Take a cleaned CC of 1×3 cm as the working electrode, a Pt sheet as the counter electrode, and Hg / HgO as the reference electrode, and perform constant potential electrodeposition in the above solution at a voltage of -0.9 V for 100 s. After the deposition, wash it with ethanol three times and dry it in a vacuum drying oven at 60°C for 6 h to obtain a Cu electrode loaded on the CC current collector (CC / Cu electrode).

[0112] Compared with Example 1, Comparative Example 2 is different in that no transition metal compound FeB is included.

[0113] Comparative Example 3NF / CoVP Electrode

[0114] The preparation method of the NF / CoVP nanoarray electrode comprises the following steps:

[0115] S1, 0.505g (1.8mmol) of cobalt sulfate heptahydrate (CoSO4·7H2O), 0.033g (0.2mmol) of vanadyl sulfate hydrate (VOSO4·xH2O) and 1.92g (32mmol) of urea (CH4N2O) were dissolved in 20mL of ultrapure water, and the mixture was stirred on a stirrer for 2h (the stirrer speed was 500rpm) to obtain a mixed solution, and then immersed in 2 pieces of 1×3cm pretreated nickel foam (NF), transferred to a high-pressure reactor, sealed and placed in a blast drying oven for solvent thermal reaction, reacted at 150°C for 5h, and allowed to cool naturally after the reaction was completed. The cooled material was washed with ultrapure water and anhydrous ethanol for 3 times respectively, and dried at 60°C in a blast drying oven for 8h to obtain the CoV-OH nanoarray precursor loaded on the NF current collector;

[0116] S2. The NF current collector-loaded CoV-OH nanoarray precursor obtained in step S1 is placed downstream in a tubular furnace, and the phosphorus source sodium dihydrogen hypophosphite is placed upstream. The mass ratio of CoV-OH to sodium dihydrogen hypophosphite is 1:20. The Ar flow rate is controlled at 2 mL / min. The temperature is increased from room temperature to 180°C at a heating rate of 2°C / min. Heat treatment is performed at 180°C for 1 h. After natural cooling, the NF current collector-loaded CoVP nanoarray electrode is obtained.

[0117] Compared with Example 2, Comparative Example 3 does not involve immersing in a copper salt solution, and the remaining steps are consistent with those of Example 2.

[0118] Comparative Example 4NF / Cu Electrode

[0119] The preparation method of the NF / Cu electrode comprises the following steps:

[0120] S1. Dissolve 10 mmol of copper acetate (Cu(CH3COO)2·H2O) in 100 mL of aqueous solution to form a uniform mixed solution.

[0121] S2. Take a clean 1×3 cm NF as the working electrode, a Pt sheet as the counter electrode, and Hg / HgO as the reference electrode, and perform constant potential electrodeposition for 300 s at a voltage of -0.5 V in the above solution. After the end, wash it with ethanol three times and dry it in a vacuum drying oven at 60°C for 6 h to obtain a Cu electrode loaded on the NF current collector;

[0122] Compared with Example 2, Comparative Example 4 is different in that there is no transition metal compound CoVP.

[0123] Comparative Example 5IF / NiScC Nanoarray Electrode

[0124] The preparation method of the IF / NiScC nanoarray electrode comprises the following steps:

[0125] S1. Dissolve 0.995 g (4 mmol) of nickel acetate tetrahydrate (NiC4H6O4·4H2O), 0.259 g (1 mmol) of scandium chloride hydrate (ScCl3·6H2O) and 1.402 g (10 mmol) of hexamethylenetetramine (HMTA) in 20 mL of ultrapure water, stir the mixture on a stirrer for 0.5 h (the stirrer speed is 500 rpm) to obtain a mixed solution, immerse 2 pieces of 1×3 cm pretreated foamed iron (IF), transfer to a high-pressure reactor, seal it and place it in a forced air drying oven for solvothermal reaction, react at 130°C for 8 h, and allow it to cool naturally after the reaction is completed. The cooled material is washed 3 times with ultrapure water and anhydrous ethanol respectively, and placed in a forced air drying oven at 60 After drying for 12 h, the NiSc-OH nanoarray precursor loaded on the IF current collector was obtained;

[0126] S2. Place the NiSc-OH nanoarray precursor loaded on the IF current collector obtained in step S1 in a tubular furnace. Under a methane atmosphere, the flow rate is controlled at 30 mL / min, and the temperature is increased from room temperature to 700°C at a heating rate of 5°C / min. Heat treatment is performed at 700°C for 2 h. After natural cooling, a NiScC nanoarray electrode loaded on the IF current collector is obtained.

[0127] Compared with Example 3, Comparative Example 5 does not involve immersing in a copper salt solution, and the remaining steps are consistent with those of Example 3.

[0128] Comparative Example 6IF / Cu Electrode

[0129] The preparation method of the IF / Cu electrode comprises the following steps:

[0130] S1. Dissolve 80 mmol of copper sulfate (CuSO4·5H2O) in 100 mL of deionized water to form a uniform mixed solution;

[0131] S2. Take a clean 1×3 cm IF as the working electrode, a Pt sheet as the counter electrode, and Hg / HgO as the reference electrode, and perform constant potential electrodeposition at -1.2 V for 500 s in the above solution. After the deposition, wash it with ethanol three times and dry it in a vacuum drying oven at 60°C for 6 h to obtain a Cu electrode loaded on the IF current collector.

[0132] Compared with Example 3, Comparative Example 6 is different in that there is no transition metal compound NiScC.

[0133] Comparative Example 7CP / FeMnCrN Nanoarray Electrode

[0134] The preparation method of the CP / FeMnCrN nanoarray electrode comprises the following steps:

[0135] S1. Take 54g (450mmol) of ferric chloride nonahydrate (Fe(NO3)3·6H2O), 6.275g (25mmol) of manganese nitrate tetrahydrate (Mn(NO3)2·4H2O), 6.75g (25mmol) of chromium chloride hexahydrate (CrCl3·6H2O) and 5.611g (100mmol) of potassium hydroxide (KOH), dissolve them in 1000mL of ultrapure water, stir them on a stirrer for 3h (the stirrer speed is 500rpm) to obtain a mixed solution, immerse 3 pieces of 6×3cm pretreated carbon paper (CP), transfer them to a high-pressure reactor, seal them and place them in a forced air drying oven for solvent thermal reaction, react at 180℃ for 12h, wait for them to cool naturally after the reaction is completed, wash the cooled material with ultrapure water and anhydrous ethanol for 3 times respectively, and dry them in a forced air drying oven at 60℃ for 12h to obtain a FeMnCr-OH nanoarray precursor loaded on the CP current collector;

[0136] S2. Place the FeMnCr-OH nanoarray precursor loaded on the CP current collector obtained in step S1 in the downstream of the tube furnace, and place urea in the upstream, the mass ratio of FeMnCr-OH to urea is 1:20, the N2 flow rate is controlled at 2 mL / min, and the temperature is increased from room temperature to 400°C at a heating rate of 5°C / min. Heat treatment is performed at 400°C for 3 hours. After natural cooling, a FeMnCrN nanoarray electrode loaded on the CP current collector is obtained.

[0137] Compared with Example 4, Comparative Example 7 does not involve immersing in a copper salt solution, and the remaining steps are consistent with those of Example 4.

[0138] Comparative Example 8CP / Cu Electrode

[0139] The preparation method of the CP / Cu electrode comprises the following steps:

[0140] S1. Dissolve 100 mmol of copper nitrate (Cu(NO3)2·3H2O) in 100 mL of anhydrous methanol to form a uniform mixed solution;

[0141] S2. Take a clean 1×3 cm CP as the working electrode, a Pt sheet as the counter electrode, and Hg / HgO as the reference electrode, and perform constant potential electrodeposition for 1000 s at a voltage of -0.7 V in the above solution. After the end, wash it with ethanol three times and dry it in a vacuum drying oven at 60°C for 6 h to obtain a Cu electrode loaded on the CP current collector;

[0142] Compared with Example 4, Comparative Example 8 is different in that it does not contain the transition metal compound FeMnCrN.

[0143] Comparative Example 9TP / CoTiWB Nanoarray Electrode

[0144] The preparation method of the TP / CoTiWB nanoarray electrode comprises the following steps:

[0145] S1, 0.125g (0.5mmol) of cobalt acetate (Co(CH3COO)2·4H2O), 0.076g (0.4mmol) of titanium chloride (TiCl4), 0.033g (0.1mmol) of sodium tungstate (Na2WO4·2H2O) and 0.561g (4mmol) of hexamethylenetetramine (HMTA) were dissolved in 30mL of ultrapure water, and the mixture was stirred on a stirrer for 1h (the stirrer speed was 500rpm) to obtain a uniform mixed solution, and then immersed in a 1×3cm pretreated titanium plate (TP), and the mixed solution was transferred to a high-pressure reactor with a polytetrafluoroethylene liner, sealed and placed in a forced air drying oven for solvent thermal reaction, reacted at 150°C for 12h, and allowed to cool naturally after the reaction was completed. The cooled material was washed with ultrapure water and anhydrous ethanol, and dried in a forced air drying oven at 60°C for 12h to obtain a TP current collector loaded CoTiW-OH nanoarray precursor;

[0146] S2. Place the TP current collector loaded with CoTiW-OH nanoarray precursor obtained in step S1 in the downstream of the tube furnace, and place the boron powder in the upstream, the mass ratio of CoTiW-OH to boron powder is 1:100, the N2 flow rate is controlled at 5 mL / min, and the temperature is increased from room temperature to 800°C at a heating rate of 2°C / min. Heat treatment is performed at 800°C for 2 hours. After natural cooling, a CoTiWB nanoarray electrode loaded on the TP current collector is obtained.

[0147] Compared with Example 5, Comparative Example 9 does not involve immersing in a copper salt solution, and the remaining steps are consistent with those of Example 5.

[0148] Comparative Example 10TP / Cu electrode

[0149] The preparation method of the TP / Cu electrode comprises the following steps:

[0150] S1. Dissolve 1 mmol of copper chloride (CuCl2·2H2O) in 100 mL of deionized water to form a uniform mixed solution.

[0151] S2. Take a clean 1×3 cm TP as the working electrode, a Pt sheet as the counter electrode, and Hg / HgO as the reference electrode, and perform constant potential electrodeposition at -0.9 V for 100 s in the above solution. After the end, wash it with ethanol three times and dry it in a vacuum drying oven at 60°C for 6 h to obtain a Cu electrode loaded on the TP current collector;

[0152] Compared with Example 5, Comparative Example 10 is different in that the transition metal compound CoTiWB is not included.

[0153] Comparative Example 11SS / NiYZrP Nanoarray Electrode

[0154] The preparation method of the SS / NiYZrP nanoarray electrode comprises the following steps:

[0155] S1. Dissolve 1.902 g (8 mmol) of nickel trichloride hexahydrate (NiCl2·6H2O), 0.304 g (1 mmol) of yttrium chloride hexahydrate (YCl3·6H2O), 0.233 g (1 mmol) of cerium chloride heptahydrate (ZrCl4·7H2O) and 1.402 g (10 mmol) of hexamethylenetetramine (HMTA) in 50 mL of ultrapure water, stir the mixture on a stirrer for 3 h (the stirrer speed is 500 rpm) to obtain a mixed solution, immerse 3 pieces of 2×3 cm pretreated stainless steel sheets (SS), transfer to a high-pressure reactor, seal it and place it in a forced air drying oven for solvothermal reaction, react at 150°C for 24 h, and allow it to cool naturally after the reaction is completed. The cooled material is washed with ultrapure water and anhydrous ethanol for 3 times respectively, and dried at 60°C in a forced air drying oven for 6 h to obtain a NiYZr-OH nanoarray precursor supported on the SS current collector;

[0156] S2. Place the SS current collector loaded with NiYZr-OH nanoarray precursor obtained in step S1 in the downstream of the tube furnace, and place red phosphorus in the upstream, the mass ratio of NiYZr to red phosphorus is 1:50, the N2 flow rate is controlled at 2 mL / min, and the temperature is increased from room temperature to 200°C at a heating rate of 3°C / min. Heat treatment is performed at 200°C for 1 h. After natural cooling, a NiYZrP nanoarray electrode loaded on the SS current collector is obtained.

[0157] Compared with Example 6, Comparative Example 11 does not involve immersing in a copper salt solution, and the remaining steps are consistent with those of Example 6.

[0158] Comparative Example 12SS / Cu Electrode

[0159] The preparation method of the SS / Cu electrode comprises the following steps:

[0160] S1. Dissolve 150 mmol of copper sulfate (CuSO4·5H2O) in 100 mL of deionized water to form a uniform mixed solution;

[0161] S2. Take a clean 1×3 cm SS as the working electrode, a Pt sheet as the counter electrode, and Hg / HgO as the reference electrode. Perform constant potential electrodeposition in the above solution at -2 V for 300 s. After the deposition, wash it with ethanol three times and dry it in a vacuum drying oven at 60°C for 6 h to obtain a Cu electrode loaded on the SS current collector.

[0162] Compared with Example 6, Comparative Example 12 is different in that it does not contain the transition metal compound NiYZrP.

[0163] Application Example 1 Performance Test of Electrocatalytic Reduction of Nitrate to Ammonia (NO3RR)

[0164] Electrochemical tests were performed using a computer-controlled electrochemical workstation (Autolab, PGSTAT302N) and a standard three-electrode system. The indicators for evaluating electrode activity were: reaching the same current density (-100 mA cm -2 )The required voltage (E), the production rate of the target product NH3 and the Faradaic efficiency.

[0165] Experimental materials: The electrocatalytic activity of the electrode was studied in a three-electrode system with the electrode prepared in Example 1, Comparative Example 1 or Comparative Example 2 (cut into 1×1 cm) as the working electrode, a Pt sheet (1×1 cm) as the counter electrode, and a Hg / HgO (immersed in 1.0 M KOH solution) electrode as the reference electrode.

[0166] Experimental method: The electrocatalytic activity test is as follows: in the above-mentioned three-electrode system, in a nitrate-containing electrolyte (electrolyte composition: 1M KOH+0.1M KNO3, pH=13.74) under stirring, the corresponding embodiment and comparative example working electrodes are scanned by CV (-0.5~-1.3V vs.Hg / HgO). After the CV scanning result is stable, the LSV curve (-0.5~-1.3V vs.Hg / HgO) is tested, and the LSV curve is compensated by 80% iR. At the same time, according to the formula E(RHE)=E(Hg / HgO)+0.0977+0.05916×pH, the potential value E(Hg / HgO) is converted to E(RHE). Then, a new nitrate-containing electrolyte was replaced, and a CA test was performed at -0.25 V vs. RHE for 30 min using the chronoamperometry (CA test). After the CA test was completed, the electrolyte was taken for ultraviolet spectrophotometry (UV-vis) to obtain the NH3 concentration in the electrolyte and calculate the ammonia production rate and Faraday efficiency.

[0167] UV-vis specific test process: After the CA test is completed, use a syringe to extract 100μL of electrolyte and inject it into 9.5mL of deionized water for dilution. Add 200μL of potassium sodium tartrate solution (500g / L) to the above solution, and finally add 200μL of Nessler's reagent. Let it stand at room temperature for 20 minutes and then test it with a UV spectrophotometer. The characteristic peak is located at 420nm. The mass concentration of NH3 in the solution can be obtained by comparing it with the prepared NH4Cl standard curve. The Faraday efficiency and yield of NH3 can be calculated as follows:

[0168]

[0169]

[0170] In the formula, NH3 FE is the Faraday efficiency of NH3; NH3 yield rate is the production rate of NH3; F is the Faraday constant (96485 C / mol); among them, is the mass concentration of NH3 in the electrolyte (g / L); V represents the total volume of the electrolyte, L; t is the electrolysis time, h; represents the molar mass of NH3, g / mol; Q represents the total charge passing through the electrode, C; A is the area of the electrode, cm 2 .

[0171] In this application example, the NO3RR performance of Example 1 (CC / FeB@Cu), Comparative Example 1 (CC / FeB), and Comparative Example 2 (CC / Cu) was tested. The LSV results are shown in Figure 7 , from Figure 7 it can be seen that for the NO3RR performance, compared with CC / Cu and CC / FeB, CC / FeB@Cu has a higher potential (E -2 ) when reaching the same current density of -100 mA·cm 100 ). E 100 are CC / Cu (-0.311 V vs. RHE) < CC / FeB (-0.191 V vs. RHE) < CC / FeB@Cu (-0.071 V vs. RHE) respectively, preliminarily indicating that CC / FeB@Cu has better nitrate reduction ability.

[0172] According to the UV-vis test, the ammonia production rate of CC / FeB@Cu is 0.958 mmol / (h·cm 2 ) at -0.25 V vs. RHE, and the Faraday efficiency is 97.2%; the ammonia production rate of Comparative Example 1 (CC / FeB) is 0.429 mmol / (h·cm 2 ) at -0.25 V vs. RHE, and the Faraday efficiency is 59.4%; while the ammonia production rate of Comparative Example 2 (CC / Cu) is 0.315 mmol / (h·cm 2 ) at the same voltage, and the Faraday efficiency is 52.1%. According to the above performance results, it can be seen that the NO3RR performance of Example 1 (CC / FeB@Cu) is better than that of Comparative Example 1 (CC / FeB) and Comparative Example 2 (CC / Cu). That is, the copper nanocluster electrode supported by the transition metal compound nanorod array prepared in the present invention has better electrocatalytic reduction ammonia performance, and its more excellent effect stems from the synergistic effect of the transition metal compound nanorod array and the copper nanoclusters.

[0173] Performance test of electrocatalytic reduction of nitrate to ammonia (NO3RR) in Application Example 2

[0174] Experimental materials: Different from Application Example 1, the working electrode was replaced with the working electrode prepared in Example 2, Comparative Example 3 or Comparative Example 4.

[0175] Experimental method: The same as that in Application Example 1.

[0176] In this application example, the NO3RR performance of Example 2 (NF / CoVP@Cu), Comparative Example 3 (NF / CoVP) and Comparative Example 4 (NF / Cu) was tested. The LSV results are shown in Figure 8 , from Figure 8 it can be seen that for the NO3RR performance, compared with NF / CoVP and NF / Cu, NF / CoVP@Cu has a higher potential (E -2 ) when reaching the same current density of -100 mA·cm 100 . E 100 are NF / Cu (-0.253 V vs. RHE) < NF / CoVP (-0.183 V vs. RHE) < NF / CoVP@Cu (-0.012 V vs. RHE) respectively, preliminarily indicating that NF / CoVP@Cu has better nitrate reduction ability.

[0177] According to the UV-vis test, the ammonia production rate of NF / CoVP@Cu is 0.989 mmol / (h·cm 2 ) at -0.25 V vs. RHE, and the Faraday efficiency is 98.6%; the ammonia production rate of Comparative Example 3 (NF / CoVP) is 0.594 mmol / (h·cm 2 ) at -0.25 V vs. RHE, and the Faraday efficiency is 71.2%; while the ammonia production rate of Comparative Example 4 (NF / Cu) is 0.412 mmol / (h·cm 2 ) at the same voltage, and the Faraday efficiency is 63.8%. According to the above performance results, it can be seen that the NO3RR performance of Example 2 (NF / CoVP@Cu) is better than that of Comparative Example 3 (NF / CoVP) and Comparative Example 4 (NF / Cu).

[0178] Performance test of electrocatalytic reduction of nitrate to ammonia (NO3RR) in Application Example 3

[0179] Experimental materials: Different from Application Example 1, the working electrode was replaced with the working electrode prepared in Example 3, Comparative Example 5 or Comparative Example 6.

[0180] Experimental method: The same as that in Application Example 1.

[0181] This application example tested the NO3RR performance of Example 3 (IF / NiScC@Cu), Comparative Example 5 (IF / NiScC), and Comparative Example 6 (IF / Cu). The LSV results are shown in Fig. 9 , and it can be seen from Fig. 9 that for the NO3RR performance, compared with IF / NiScC and IF / Cu, when reaching the same current density of -100 mA·cm -2 , the potential (E 100 ) is higher. E 100 are IF / Cu (-0.252 V vs. RHE) < IF / NiScC (-0.148 V vs. RHE) < IF / NiScC@Cu (-0.043 V vs. RHE) respectively, preliminarily indicating that IF / NiScC@Cu has better nitrate reduction ability.

[0182] According to the UV-vis test, the ammonia production rate of IF / NiScC@Cu is 1.126 mmol / (h·cm 2 ) at -0.25 V vs. RHE, and the Faraday efficiency is 97.9%; while for Comparative Example 5 (IF / NiScC), the ammonia production rate is 0.699 mmol / (h·cm 2 ) at -0.4 V vs. RHE, and the Faraday efficiency is 72.1%; while for Comparative Example 6 (IF / Cu), the ammonia production rate is 0.381 mmol / (h·cm 2 ) at the same voltage, and the Faraday efficiency is 52.4%. According to the above performance results, it can be seen that the NO3RR performance of Example 3 (IF / NiScC@Cu) is better than that of Comparative Example 5 (IF / NiScC) and Comparative Example 6 (IF / Cu).

[0183] Performance test of electrocatalytic reduction of nitrate to ammonia (NO3RR) in Application Example 4

[0184] Experimental materials: Different from Application Example 1 in that the working electrode is replaced with the working electrode prepared in Example 4, Comparative Example 7, or Comparative Example 8.

[0185] Experimental method: The same as Application Example 1.

[0186] This application example tested the NO3RR performance of Example 4 (CP / FeMnCrN@Cu), Comparative Example 7 (CP / FeMnCrN), and Comparative Example 8 (CP / Cu). The LSV results are shown in Fig.10 , and it can be seen from Fig.10 that for the NO3RR performance, compared with CP / FeMnCrN and CP / Cu, when reaching the same current density of -100 mA·cm -2The potential (E 100 ) is higher, and E 100 are CP / Cu (-0.261 V vs. RHE) < CP / FeMnCrN (-0.112 V vs. RHE) < CP / FeMnCrN@Cu (0.019 V vs. RHE) respectively, preliminarily indicating that CP / FeMnCrN@Cu has better nitrate reduction ability.

[0187] According to the UV-vis test, the ammonia production rate of CP / FeMnCrN@Cu is 1.297 mmol / (h·cm 2 ) at -0.25 V vs. RHE, and the Faraday efficiency is 99.1%; while for Comparative Example 7 (CP / FeMnCrN), the ammonia production rate is 0.687 mmol / (h·cm 2 ) at -0.25 V vs. RHE, and the Faraday efficiency is 76.2%; for Comparative Example 8 (CP / Cu), the ammonia production rate is 0.441 mmol / (h·cm 2 ) at the same voltage, and the Faraday efficiency is 56.8%. According to the above performance results, it can be seen that the NO3RR performance of Example 4 (CP / FeMnCrN@Cu) is superior to that of Comparative Example 7 (CP / FeMnCrN) and Comparative Example 8 (CP / Cu).

[0188] Performance test of electrocatalytic reduction of nitrate to ammonia (NO3RR) in Application Example 5

[0189] Experimental materials: Different from Application Example 1 in that the working electrode is replaced with the working electrode prepared in Example 5, Comparative Example 9 or Comparative Example 10.

[0190] Experimental method: The same as Application Example 1.

[0191] In this application example, the NO3RR performance of Example 5 (TP / CoTiWB@Cu), Comparative Example 9 (TP / CoTiWB) and Comparative Example 10 (TP / Cu) was tested. The LSV results are shown in Fig.11 , and from Fig.11 it can be seen that for the NO3RR performance, compared with TP / CoTiWB and TP / Cu, TP / CoTiWB@Cu has a higher potential (E -2 ) when reaching the same current density of -100 mA·cm 100 , and E 100 are TP / Cu (-0.131 V vs. RHE) < TP / CoTiWB (-0.234 V vs. RHE) < TP / CoTiWB@Cu (-0.009 V vs. RHE) respectively, preliminarily indicating that TP / CoTiWB@Cu has better nitrate reduction ability.

[0192] According to the UV-vis test, the ammonia production rate of TP / CoTiWB@Cu was 1.377 mmol / (h·cm 2 ), and the Faraday efficiency was 99.6%; while for Comparative Example 9 (TP / CoTiWB), the ammonia production rate was 0.845 mmol / (h·cm 2 ), and the Faraday efficiency was 76.3%; for Comparative Example 10 (TP / Cu), the ammonia production rate was 0.362 mmol / (h·cm 2 ) at the same voltage, and the Faraday efficiency was 47.5%. According to the above performance results, it can be seen that the NO3RR performance of Example 5 (TP / CoTiWB@Cu) is better than that of Comparative Example 9 (TP / CoTiWB) and Comparative Example 10 (TP / Cu).

[0193] Performance test of electrocatalytic reduction of nitrate to ammonia (NO3RR) in Application Example 6

[0194] Experimental materials: Different from Application Example 1, the working electrode was replaced with the working electrode prepared in Example 6, Comparative Example 11 or Comparative Example 12.

[0195] Experimental method: The same as Application Example 1.

[0196] In this application example, the NO3RR performance of Example 6 (SS / NiYZrP@Cu) and Comparative Example 11 (SS / NiYZrP), Comparative Example 12 (SS / Cu) was tested. See the LSV results Fig.12 , and from Fig.12 it can be seen that for the NO3RR performance, compared with SS / NiYZrP and SS / Cu, SS / NiYZrP@Cu has a higher potential (E -2 ) when reaching the same current density of -100 mA·cm 100 ), and E 100 are SS / Cu (-0.327 V vs. RHE) < SS / NiYZrP (-0.152 V vs. RHE) < SS / NiYZrP@Cu (0.052 V vs. RHE) respectively, preliminarily indicating that SS / NiYZrP@Cu has better nitrate reduction ability.

[0197] According to the UV-vis test, the ammonia production rate of SS / NiYZrP@Cu was 1.464 mmol / (h·cm 2 ), and the Faraday efficiency was 99.8%; while for Comparative Example 11 (SS / NiYZrP), the ammonia production rate was 0.923 mmol / (h·cm 2), the Faraday efficiency is 77.6%; while the ammonia generation rate of comparative example 12 (SS / Cu) at the same voltage is 0.403mmol / (h·cm 2 ), and the Faraday efficiency is 51.2%. According to the above performance results, it can be seen that the NO3RR performance of Example 6 (SS / NiYZrP@Cu) is better than that of Comparative Example 11 (SS / NiYZrP) and Comparative Example 12 (SS / Cu).

[0198] Based on the electrocatalytic nitrate reduction to ammonia activity of the above embodiments, the copper nanocluster electrode loaded with the transition metal compound nanoarray prepared by the present invention has better electrocatalytic reduction of ammonia performance, and its more excellent effect is derived from the synergistic effect of the transition metal compound nanoarray and the copper nanoclusters. The copper nanocluster electrode loaded with the transition metal compound nanoarray prepared by the present invention has great application prospects in NO3RR.

[0199] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a transition metal compound nanoarray-loaded copper nanocluster electrode, comprising the following steps: S1, placing the current collector in a mixed solution containing a transition metal salt and a precipitant, performing a solvothermal reaction, and post-processing to obtain a nanoarray precursor; S2, taking the nanoarray precursor obtained in step S1, adding a heat conversion source material and calcining it under oxygen-free conditions to obtain a transition metal compound nanoarray material; S3, taking the transition metal compound nanoarray material obtained in step S2, and soaking it in a copper salt solution to obtain a transition metal compound nanoarray-loaded copper nanocluster electrode; In step S2, the heat conversion source material is a boron source, a carbon source, a nitrogen source or a phosphorus source.

2. The preparation method according to claim 1, characterized in that: In step S1, the transition metal in the transition metal salt is selected from at least one of Ni, Co, Fe, Mn, Sc, Ti, V, Cr, Cu, Mo, Cd, W, Y, Zr, Ce, Ga, In, Ge, and Sn.

3. The preparation method according to claim 1, characterized in that: In step S1, the precipitant is selected from at least one of sodium hydroxide, potassium hydroxide, ammonia water, sodium carbonate, sodium bicarbonate, urea, hexamethylenetetramine, and sodium oxalate.

4. The preparation method according to claim 1, characterized in that: In step S1, the current collector is carbon cloth, carbon paper or metal current collector.

5. The preparation method according to claim 1, characterized in that: In step S1, the temperature of the solvent thermal reaction is 50-250°C.

6. The preparation method according to claim 1, characterized in that: In step S2, the calcination temperature is 180-1000°C.

7. The preparation method according to claim 1, characterized in that: In step S3, the copper salt is one or more of copper sulfate, copper nitrate, copper chloride or copper acetate.

8. A copper nanocluster electrode loaded with a transition metal compound nanoarray prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the transition metal compound nanoarray-supported copper nanocluster electrode according to claim 8 in the electrocatalytic nitrate reduction reaction to produce ammonia.

10. Use of the transition metal compound nanoarray-supported copper nanocluster electrode according to claim 8 in electrochemical treatment of nitrate-containing wastewater.